Active middle ear implants: Vibroplasty™ in children and adolescents with acquired or congenital middle ear disorders. (June 2013) - Clarós, Pedro; Pujol, Ma del Carmen
Abstract Conclusion: Active middle ear implant (AMEI) implantation in children and adolescents is safe and provides improved hearing results. No statistical difference in hearing outcomes was shown in the group of patients affected by chronic middle ear diseases versus aural atresia. Also, the transducer location (round window versus oval window placement) did not lead to different outcomes in hearing abilities. Objectives: (1) To assess the hearing outcomes with the active implant Vibrant Soundbridge (VSB) in children and adolescents. (2) To evaluate whether functional results of the subjects in the study could depend on the hearing loss etiology (chronic middle ear diseases versus aural atresia) or on transducer location (round window versus oval window placement). Methods: The study was carried out with a retrospective, single-subject, repeated measures design, and included 22 children and adolescents with conductive or mixed hearing loss due to aural atresia or chronic middle ear diseases. Preoperative and postoperative pure tone air conduction (AC) and bone conduction (BC) thresholds were measured to demonstrate implantation safety. Free-field warble tone and speech audiometry were performed to assess postoperative hearing abilities with and without the VSB. Results: No significant changes in mean BC or AC thresholds between preoperative and postoperative conditions were seen in the 22 patients. Mean PTA4 functional gain was 30.7 dB. Averaged over all 22 patients, word recognition at 65 dB SPL changed from an average of 19% in the unaided postoperative condition to 97% in the VSB-aided condition. Functional results were independent of hearing loss etiology and transducer location.